الصراع الحضري بين الغرب والشرق في ميزان الإسلام - شمس البحر أندي غاليغو; Shams Al-Bahr Andi Ghalighu (2024)
The clash between the East and the West is one of the phenomenon of the end of time. It is defined as the clash between the understanding and faith and thus, have a direct relation with Islam and other religion in the world. The clash of culture between the West and Islam had always existed since the Crusades. Recently this has given rise to the globalization era. Howeve< the concept of globalization proposed by the West may not be equivalent to alamijyah which is the Islamic equivalent to term which was taught by Islam some fourteen centuries ago. Hence, the noted principle of "al-Islam Ya'lu Wala Yu'la Alaih" will always be relevant for the development of human and time.